1999
DOI: 10.1177/112067219900900209
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m Labeled Red Blood Cells Scintigraphy: A Diagnostic Method for Orbital Cavernous Hemangioma

Abstract: Tc-99m RBC scintigraphy is a reliable method for diagnosing orbital cavernous hemangioma. It should be included in our arsenal of diagnostic techniques, particularly for cases which are otherwise difficult to diagnose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Tc red blood cells is commonly used in the evaluation of hepatic hemangiomas and may also be used in the noninvasive evaluation of extrahepatic vascular lesions such as vascular tumors of the orbit, [13][14][15][16][17][18] as well as in gastrointestinal bleeding imaging, cardiacgated blood pool studies, and radionuclide venograms.…”
Section: Scintigraphy With 99mmentioning
confidence: 99%
See 1 more Smart Citation
“…Tc red blood cells is commonly used in the evaluation of hepatic hemangiomas and may also be used in the noninvasive evaluation of extrahepatic vascular lesions such as vascular tumors of the orbit, [13][14][15][16][17][18] as well as in gastrointestinal bleeding imaging, cardiacgated blood pool studies, and radionuclide venograms.…”
Section: Scintigraphy With 99mmentioning
confidence: 99%
“…These 2 cases displayed increased uptake within the lesion on SPET images (AI=4.94 and 3.68, respectively), which is probably due to the vascular nature of these tumors. 18 Therefore, in these cases the SPET images need to be integrated with data regarding clinical preoperative evaluation (anamnestic evaluation of onset and pain, careful palpation of the globe, and ocular motility study) and CT scans or MRI studies.…”
Section: Scintigraphy With 99mmentioning
confidence: 99%
“…In some studies, this typical appearance of these tumors was used for the differentiation from malignant tumors and confirmed with histopathology (5). According to previous reports, Tc 99m labeled erythrocyte imaging could differentiate hemangioma from malignant tumors (5,8,9,10). This characteristic of Tc 99m labeled erythrocyte scintigraphy might help to decide the choice of treatment, i.e.…”
Section: Discussionmentioning
confidence: 80%
“…Radioactivity accumulation within the lesion of our patient was very prominent in the late phase images. The scintigraphic pattern of the hemangioma which is hypoactive in the vascular phase and hyperactive in the late phase, is previously well established (8,9,10). In some studies, this typical appearance of these tumors was used for the differentiation from malignant tumors and confirmed with histopathology (5).…”
Section: Discussionmentioning
confidence: 94%
“…Sayit et al 9 reported that, in all patients with OCH whom they studied, the preoperative diagnosis was confirmed by the typical pattern of perfusion blood pool mismatch on the 99m Tc-RBC scintigraphy. Gdal-On et al 10 performed 99m Tc-RBC scintigraphy on 12 patients with OCH, all of whom were confirmed by means of histology. Polito et al 11 performed 99m Tc-RBC scintigraphy on 23 patients affected by an orbital mass previously revealed with CT and MRI and suggesting cavernous hemangioma.…”
Section: Discussionmentioning
confidence: 99%